2015
DOI: 10.1371/journal.pone.0134953
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Vibrio spp in Karstic Coastal Marshes in the Yucatan Peninsula

Abstract: Coastal bodies of water formed by the combination of seawater, underground rivers and rainwater comprise the systems with the greatest solar energy flow and biomass production on the planet. These characteristics make them reservoirs for a large number species, mainly microorganisms. Bacteria of the genus Vibrio are natural inhabitants of these environments and their presence is determined by variations in the nutrient, temperature and salinity cycles generated by the seasonal hydrologic behavior of these lago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…in the present study were Vibrio fortis, Vibrio alginolyticus, and Vibrio hyugaensis, which suggested that the predominance of a specific Vibrio sp. seems to be site-specific as others have reported different predominant Vibrio species in their studies, such as V. alginolyticus, Vibrio campbellii, Vibrio carchariae, Vibrio harveyi, Vibrio owensii, Vibrio parahaemolyticus, Vibrio rotiferianus, and Vibrio splendidus (Maeda et al, 2003;Eiler et al, 2006;Ortiz-Carrillo et al, 2015;Li et al, 2019;Wong et al, 2019). The four major clinically important pathogenic Vibrio species, Vibrio cholerae, V. parahaemolyticus, V. alginolyticus, and Vibrio vulnificus, have been implicated in human diseases such as gastroenteritis and septicemia and even death in immunocompromised patients (Novoslavskij et al, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…in the present study were Vibrio fortis, Vibrio alginolyticus, and Vibrio hyugaensis, which suggested that the predominance of a specific Vibrio sp. seems to be site-specific as others have reported different predominant Vibrio species in their studies, such as V. alginolyticus, Vibrio campbellii, Vibrio carchariae, Vibrio harveyi, Vibrio owensii, Vibrio parahaemolyticus, Vibrio rotiferianus, and Vibrio splendidus (Maeda et al, 2003;Eiler et al, 2006;Ortiz-Carrillo et al, 2015;Li et al, 2019;Wong et al, 2019). The four major clinically important pathogenic Vibrio species, Vibrio cholerae, V. parahaemolyticus, V. alginolyticus, and Vibrio vulnificus, have been implicated in human diseases such as gastroenteritis and septicemia and even death in immunocompromised patients (Novoslavskij et al, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…The distribution of Vibrio spp. is influenced by various environmental parameters (in particular temperature, salinity and nutrients) and biological factors (Ortiz-Carrillo et al, 2015;Zhang et al, 2018). A shift in the Vibrio communities in relation to seasonal variations and fluctuations of environmental parameters (principally temperature and salinity) have been widely evidenced (Tamplin, 2001;Lin and Schwarz, 2003;Froelich et al, 2012;Johnson et al, 2012;Oliver, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria belonging to the genus Vibrio can be considered as indigenous in marine environments, where they are ubiquitous in a number of different environments (including estuaries, open ocean and deep-sea) and promptly adapting to environmental changes due to high genome plasticity (Oberbeckmann et al, 2012;King et al, 2019). This genus is highly heterogeneous and includes microorganisms found either as free-living or associated with particles and/or with a wide range of aquatic organisms, as mutualistic symbionts or pathogens (Ortiz-Carrillo et al, 2015;Siboni et al, 2016). Various species cause diseases in aquatic animals (constituting also a serious problem in aquaculture, where infections cause significant losses in stock and profit) and/or humans (Pruzzo et al, 2005;King et al, 2019. Human pathogenic Vibrio spp.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of Vibrio strains as probiotics has been widely reported. The reason for its use is because this bacterial group has a number of characters needed by a probiotic (Ortiz-Carillo et al, 2015) in an aquaculture system, including being able to compete with other bacteria (Thompson et al, 2010), add nutrition by providing essential nutrients, can improve digestibility by releasing essential enzymes (Lin et al, 2018) has the ability to colonize the digestive tract and host body (Gomez-Gil et al, 2014), and can produce substances that inhibit the growth of opportunistic pathogenic bacteria (Pereire et al, 2018).…”
Section: Introductionmentioning
confidence: 99%